Effect of Speed Agility Training and Quickness on Speed Enhancement and Agility: an Experimental Study - Furqon Fauzi Wijaya; Pungki Indarto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research was conducted at Senior High School 1 Wonogiri. The sample taken was the women's futsal extracurricular group of Senior High School 1 Wonogiri which totaled 17 students. The data collection technique used is the use of tests and measurements. As for the measurement test procedure, researchers use Speed and agility measurement tests. The test instruments used are the 30 meter running test and the shuttle run.  Hasil of this study obtained the value of sig. (The 2-tailed) the treatment group was 0.000. The value of the sig. The (2-tailed) treatment group < 0.05 showed that there was a significant difference between the initial test and the final test. So it can be concluded that speed agility and quickness training affects the level of speed and agility of the women's futsal extracurricular group of Senior High School 1 Wonogiri.